Convective thermohydraulic heat transfer enhancement of mixed dimpled geometries in rectangular channel - S.A. Aasa (Elsevier, 2022)
Various interior techniques to enhance the local heat transfer are essential for improved performance of appliances. The high-pressure penalties created by these applied passive techniques cause high power consumption and lower the pumping power. This research presents the simulation of four (4) different compound angled dimples, which are presented in this research; Case 1: 90-Circular-45-Oval dimple (90-C-45-O); Case 2: 45-Oval-90-Circular dimple (45-O-90C); Case 3: 60-Oval-90-Circular dimple (60-O-90-C); Case 4: 90-Circular-60-Oval dimple (90-C-60-O). The oval dimple print diameter, D = 20 mm, and the circular dimple print diameter, d = 10 mm. The objectives are to investigate the influence of mixed geometries with varying locations and orientation angles of the dimples. The pressure drops and heat transfer measurements are extracted using the Star-CCM+ CFD simulation bench RANS model. It was revealed that friction factor ratio, (f/fo) increases with the Reynolds number, and at the minimum of Re 1000, a 25% increment is observed, while 71% increment is noted for 11,000 Re. Case 2 has optimal effects compared to cases 3, 2 and 1. The Nusselt number ratio (Nu/Nuo) increases with Re with at least a 26% increment at 1000 Re for Case 1. Case 4 dimple arrangement is observed to be least performing arrangement with 12 – 22% Nusselt number increment. Also, the thermal performance quantified by (Nu/Nuo) / (f/fo)1/3 is the highest for the angle of Case 2 for all Re > 2000. The results thus contribute to engineering applications with thermal performance based on varying angle, and heat transfer enhancement.